Market-specific and currency-specific risk during the global financial crisis: Evidence from the interbank markets in Tokyo and London - Fukuda, Shin-ichi (Journal of Banking & Finance, 2012)
This paper investigates how international money markets reflected credit and liquidity risk during the global financial crisis. After matching the currency denomination, we examine how the Tokyo Interbank Offered Rate (TIBOR) was synchronized with the London Interbank Offered Rate (LIBOR). We find remarkably asymmetric responses in market-specific and currency-specific risk during the crisis. The regression results suggest that market-specific credit risk increased the difference across markets, whereas liquidity risk caused the difference across currency denominations. They also support the view that liquidity shortage of the US dollar occurred in international money markets during the crisis. Coordinated central bank liquidity provisions were useful in reducing the liquidity shortage of the US dollar, but their effectiveness was asymmetric across markets.